THE ROLE OF THE TNF-α GENE POLYMORPHIC VARIANT IN THE DEVELOPMENT OF PSORIASIS IN CHILDREN (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This study explores the genetic aspects of the etiopathogenesis of psoriasis in children. The research analyzed the distribution of alleles and genotypes of the single nucleotide polymorphism -308G>A of the TNF-α gene (rs1800629) in 107 affected children and 80 individuals in a control group. The results demonstrated a statistically significant prevalence of the heterozygous G/A genotype and the A allele in the patient group compared to the control group, which is associated with an almost twofold increase in the risk of disease development (OR=1.9). It was established that the presence of the A allele is associated with high TNF-α production and can serve as a genetic marker of susceptibility to psoriasis, whereas the G/G genotype plays a protective role. The findings suggest that the -308G>A polymorphism is a potential biomarker for risk prediction and assessment of psoriasis severity in pediatric practice.
Keywords: psoriasis, children, TNF-α gene, genetic polymorphism, pathogenesis, allele, genotype.